Impact of Number of Artificial Ants in ACO on Network Convergence Time: A Survey - Lusweti, Samuel W; Odoyo, Collins O; A Rambim, Dorothy (Universitas Komputer Indonesia, 2022)
Due to the dynamic nature of computer networks today, there is need to make the networks self-organized. Selforganization can be achieved by applying intelligent systems in the networks to improve convergence time. Bio-inspired algorithms that imitate real ant foraging behaviour of natural ants have been seen to be more successful when applied to computer networks to make the networks self-organized. In this paper, we studied how Ant Colony Optimization (ACO) has been applied in the networks as a bio-inspired algorithm and its challenges. We identified the number of ants as a drawback to guide this research. We retrieved a number of studies carried out on the influence of ant density on optimum deviation, number of iterations and optimization time. We found that even though some researches pointed out that the numbers of ants had no effect on algorithm performance, many others showed that indeed the number of ants which is a parameter to be set on the algorithm significantly affect its performance. To help bridge the gap on whether or not the number of ants were significant, we gave our recommendations based on the results from various studies in the conclusion section of this paper